2021
DOI: 10.1038/s41598-020-77188-7
|View full text |Cite
|
Sign up to set email alerts
|

Assumptions about fence permeability influence density estimates for brown hyaenas across South Africa

Abstract: Wildlife population density estimates provide information on the number of individuals in an area and influence conservation management decisions. Thus, accuracy is vital. A dominant feature in many landscapes globally is fencing, yet the implications of fence permeability on density estimation using spatial capture-recapture modelling are seldom considered. We used camera trap data from 15 fenced reserves across South Africa to examine the density of brown hyaenas (Parahyaena brunnea). We estimated density an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
0
9
2
Order By: Relevance
“…The highest recorded densities are from reserves in Namibia (Okonjima Nature Reserve; Edwards et al, 2019), South Africa (Kwandwe Nature Reserve; Welch & Parker, 2016), and the central Tuli block, Botswana (Vissia et al, 2021). These far exceed our density estimate (Supplementary Table 2), although assumptions about fence permeability may account for some of these differences (Williams et al, 2021). Although there are challenges in comparing density estimates given some of the methods used (occupancy models and track counts; Balme et al, 2009; Rich et al, 2014; Rogan et al, 2019), our densities are similar to brown hyaena densities in similar habitats where spatial capture–recapture methods have been used (Williams et al, 2021; Fig.…”
Section: Discussioncontrasting
confidence: 67%
“…The highest recorded densities are from reserves in Namibia (Okonjima Nature Reserve; Edwards et al, 2019), South Africa (Kwandwe Nature Reserve; Welch & Parker, 2016), and the central Tuli block, Botswana (Vissia et al, 2021). These far exceed our density estimate (Supplementary Table 2), although assumptions about fence permeability may account for some of these differences (Williams et al, 2021). Although there are challenges in comparing density estimates given some of the methods used (occupancy models and track counts; Balme et al, 2009; Rich et al, 2014; Rogan et al, 2019), our densities are similar to brown hyaena densities in similar habitats where spatial capture–recapture methods have been used (Williams et al, 2021; Fig.…”
Section: Discussioncontrasting
confidence: 67%
“…Although our analysis was based on the BVC fence being impermeable, we are confident that our results were not affected by this bias as the fence is checked and maintained on a daily basis. In addition, the size of the Main Conservancy is >1000 km 2 , a supporting factor considering that the degree of overestimation was found to be inversely proportional to reserve size (Williams et al, 2021). In the case of Ripple Creek, estimated abundance was the same as the number of separate individuals identified in the identification process.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, we are confident that any potential bias is likely to be negligible. Recent research on the effect of fence permeability assumptions on brown hyaena density estimates has also highlighted how density can be significantly overestimated when fences are incorrectly assumed to be impermeable (Williams et al, 2021). Although our analysis was based on the BVC fence being impermeable, we are confident that our results were not affected by this bias as the fence is checked and maintained on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As bone scavengers often have large home ranges and opportunistically transverse fence boundaries, it is possible that some of the nutrients from lion carcasses are lost from the reserve. However, Williams et al (2021) showed that in reserves where fence integrity is high, scavengers such as brown hyaena generally remain within the reserve due to the abundance of sympatric predators and high levels of carrion, so the loss of nutrients via this vector is assumed negligible.…”
Section: Role Of Predators and Bone Scavengersmentioning
confidence: 99%